Compassionate use of the PASCAL transcatheter mitral valve repair system for patients with severe mitral regurgitation: a multicentre, prospective, observational, first-in-man study. Issue 10096 (19th August 2017) - Praz, Fabien; Spargias, Konstantinos; Chrissoheris, Michael; Büllesfeld, Lutz; Nickenig, Georg; Deuschl, Florian; Schueler, Robert; Fam, Neil P; Moss, Robert; Makar, Moody; Boone, Robert; Edwards, Jeremy; et al.
Summary: Background: Severe mitral regurgitation is associated with impaired prognosis if left untreated. Using the devices currently available, transcatheter mitral valve repair (TMVr) remains challenging in complex anatomical situations. We report the procedural and 30-day results of the first-in-man study of the Edwards PASCAL TMVr system. Methods: In this multicentre, prospective, observational, first-in-man study, we collected data from seven tertiary care hospitals in five countries that had a compassionate use programme in which patients underwent transcatheter mitral valve repair using the Edwards PASCAL TMVr system. Eligible patients were those with symptomatic, severe functional, degenerative, or mixed mitral regurgitation deemed at high risk or inoperable. Safety and efficacy of the procedure were prospectively assessed at device implantation, discharge, and 30 days after device implantation. The key study endpoints were technical success assessed at the end of the procedure and device success 30 days after implantation using the Mitral Valve Academic Research Consortium definitions. Findings: Between Sept 1, 2016, and March 31, 2017, 23 patients (median age 75 years [IQR 61–82]) had treatment for moderate-to-severe (grade 3+) or severe (grade 4+) mitral regurgitation using the Edwards PASCAL TMVr system. At baseline, the median EuroScore II score was 7·1% (IQR 3·6–12·8) and the median Society of Thoracic Surgeons predicted risk of mortality for mitral valve repair was 4·8% (2·1–9·0) and 6·8% (2·9–10·1) for mitral valve replacement. 22 (96%) of 23 patients were New York Heart Association (NYHA) class III or IV at baseline. The implantation of at least one device was successful in all patients, resulting in procedural residual mitral regurgitation of grade 2+ or less in 22 (96%) patients. Six (26%) of 23 patients had two implants. Periprocedural complications occurred in two (9%) of 23 patients (one minor bleeding event and one transient ischaemic attack). Despite the anatomical complexity of mitral regurgitation in the patients in this compassionate use cohort, technical success was achieved in 22 (96%) of 23 patients, and device success at 30 days was achieved in 18 (78%) patients. Three patients (13%) died during the 30 day follow-up. 19 (95%) of 20 patients alive 30 days after implantation were NYHA class I or II. Interpretation: This study establishes feasibility of the Edwards PASCAL TMVr system with a high rate of technical success and reduction of mitral regurgitation severity. Further research is needed on procedural and long-term clinical outcomes. Funding: None.